Assessment of Food Safety and Food Handling Practice Knowledge among College of Basic Education Students, Kuwait - Fatemah Ashkanani; Wafaa Husain; Maryam A Al Dwairji (Journal of Food Quality)
The aim of this study is to assess the overall food safety knowledge of students at the College of Basic Education in Kuwait and to explore the relationship between their knowledge and demographic characteristics. A valid questionnaire was used that included 16 food handling practice (FHP) questions and 15 food safety knowledge (FSK) questions. Each question had one correct answer that was awarded a score of one point, while a score of zero was given for all incorrect answers. In addition, a passing percentage was calculated. A passing percentage is the percentage of participants who answered correctly ≥ 50% of the questions. A total of 585 students participated in the study (mean age = 21.3 ± 3.88 years). The results showed that the mean score of FHP was 7.56 ± 1.96 (47.2%), with the highest mean practices being using a paper towel to dry hands and washing hands before cooking or eating (91.5% and 90.1%, resp.). The lowest mean practices (5.3%) were checking the temperature of burgers followed by (6%) the way of defrosting meat. The mean score of FSK was 3.44 ± 2.00 (22.9%), with the highest mean knowledge (63.8%) being related to cleaning the kitchen counter. The lowest mean knowledge (6.8%) was related to the optimum growth temperature for the most disease-causing bacteria. The overall passing percentage of FHP was 55%, while it was 2.9% for FSK. The results obtained showed that the students with the highest FHP scores were generally female, aged ≥ 28 years, and single, and they cook by themselves all the time or sometimes (p<0.001, p<0.001, p<0.001, and p=0.004, resp.). The students with the highest FSK scores were generally male and they cook by themselves all the time or sometimes (p=0.018 and p=0.002, resp.). In conclusion, the study showed that students had insufficient scores for FHP and FSK. Therefore, an effective food safety education programme is urgently needed.